National incidence of traumatic spinal fractures in China: Data from China National Fracture Study. Issue 35 (August 2018) - Liu, Bo; Zhu, Yanbin; Liu, Song; Chen, Wei; Zhang, Fei; Zhang, Yingze
Abstract : Abstract: To provide a basis for disease prevention, this article aimed to clarify the incidence and risk factors of traumatic fractures in China. The China National Fracture Study (CNFS) was a retrospective epidemiological study that recruited a nationally representative sample from 8 provinces, 24 urban cities, and 24 rural counties in China using stratified random sampling and the probability proportional to size method. A total of 512, 187 individuals were involved in CNFS. Incidence rates for traumatic spinal fractures were estimated from the database of CNFS. The distributions by age and sex; as well as by demographic factors such as ethnic origin, occupation, and geographical region were also analyzed. The potential risk factors for traumatic spinal fractures were also identified, such as gender, age, ethnic origin, education, occupation, cigarette smoking, alcohol drinking, calcium or vitamin D taking, body mass index (BMI), sleep time per day, history of previous fracture, and urbanization. This study is registered with the Chinese Clinical Trial Registry, number ChiCTR-EPR-15005878. Around 168 individuals (92 men and 76 women, mean age 55.36 ± 16.19 years) reported 178 (10 individuals with 2 segments) segments of spinal fractures that had occurred in 2014. The incidence rate for traumatic spinal fractures was 32.80 per 100, 000 people. Stratified by occupation, retired and unemployed individuals had the highest incidence rates: 72.45 (42.19–102.71) and 64.08 (36.68–91.48) per 100, 000 people. According to education level, illiterate individuals had the highest incidence rate (73.39, 54.00–92.79 per 100, 000 population). Among all age groups, fractures of thoracolumbar vertebra (T11-L2) were the most common for both sexes, followed by fractures of lumbar vertebra (L3–L5). Four independent risk factors for traumatic spinal fractures were found, including aging, alcohol drinking, sleeping <7 hours per day, and having a previous fracture history. The current study provides detailed information about the national incidence of traumatic spinal fractures, distribution, and risk factors. Aging, alcohol drinking, sleeping <7 hours per day, and having a previous fracture history were the independent risk factors for traumatic spinal fractures in China.